Use of alternative aggregates for the production of hot-mix asphalt surface layers: A performance evaluation. (22nd August 2022) - Raschia, Simone; Tattolo, Stefano
Highlights: Bailey method is a suitable mix design method for anti-skid HMA surface layers. A new laboratory procedure is able to characterize skid resistance evolution. The use of alternative aggregates did not penalize HMA mechanical properties. The production of one mixture was validated in a production asphalt plant. Abstract: The decreasing availability of virgin mineral aggregates is a critical issue related to the production of asphalt pavements. For this reason, several alternatives have been recently taken into account by the scientific community to recycle and re-use waste and secondary materials to obtain hot-mix asphalt (HMA) materials equally valid. When dealing with surface layers, stiffness, rutting and skid resistance, are fundamental performance to ensure safety and comfort to the user. This study deals with a performance evaluation of HMA surface layer materials (in laboratory and in plant) produced with alternative aggregates, such as steel slag, expanded clay and municipal solid waste sand.